Pengaruh Jenis Biochar dan Kompos terhadap Aktivitas Mikroorganisme Tanah - Soniari, Ni Nengah; Sutari, Ni Wayan Sri; Pradnyawathi, Ni Luh Made (Agrotrop : Journal on Agriculture Science; Vol 13 No 3 (2023)DO - 10.24843/AJoAS.2023.v13.i03.p08, 2023)
The Effect of Biochar Types and Compost on Soil Microorganism Activities. This research was carried out at the plastic house of Pasraman Unud Jimbaran from January to June 2021. The type of biochar used come from waste materials such as bamboo, rice husks, coconut shells, and corn cobs, while the compost was selected according to Indonesian National Standards. The purpose of this study was to determine the biochar material from several wastes combined with compost in supporting the activity of soil microorganisms as well as the N, P, K, pH and C-organic soil. The experimental design used in this study was a Simple Completely Randomized Design with 9 treatments and 3 replications so that it became 27 experimental units. The experimental treatments consisted of: B0 (control); B1 (1.5% rice husk biochar/ha); B2(1,5% biochar bamboo/ha); B3 (1.5% corncob biochar/ha); B4 (1.5% coconut shell biochar/ha); B5 (0.75% rice husk biochar + 0.75% compost)/ha; B6 (0.75% bamboo biochar + 0.75% compost)/ha; B7 (0.75% corncob biochar + 0.75% compost)/ha; B8 (0.75% coconut shell biochar + 0.75% compost/ha). Monitoring of media humidity is carried every 2 days and stirring once a week. Observations were made at the end of the incubation period (35 days) on soil respiration, C-organic, N-total and pH. The results showed that the highest activity of microorganisms occurred in the B6 treatment (0.75% bamboo biochar + 0.75% compost)/ha. The addition of (biochar + compost) to the soil gave a significantly different effect on organic C and total soil N.